Evaluasi dan Desain Ulang Electrical Submersible Pump (ESP) Pada Sumur “YS-19” Lapangan Sumatera Selatan - Suhartono, Yudi; Wiyono, Joko; Firdaus, Firdaus; Wicaksono, Bambang; Manik, Nijusiho; Pradana, Michael A. (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Over time, the production process is ensured to decrease, causing the production rate to be reduced or not optimal and the way to optimize the production well is to use one of the artificial methods or Artificial Lift. The Electrical Submersible Pump is one alternative to help pour the pump into motion by an electric motor. The method used is the 3 phase Wiggins Inflow Performance Relationship (IPR) method. The Wiggins method is a development method from the Vogel method which assumes that each phase can be carried out separately so that the water rate (Qw) and oil rate (Qo) can be calculated respectively. each. The writing methodology used in this paper is carried out using well data, well production data, and other supporting data. The results of the IPR curve analysis from manual calculations can be said thatThe “YS-19” well has a Maximum Flow Rate (Qtotal) of 2944 BFPD. After pairing the REDA pump type with the ESP type D2400N 60Hz 3500 rpm with a Head/Stage of 25 ft/stage, the HP/stage value is 0.52 HorsePower (HP), Pump Setting Depth of 2242.96 ft with Pump Intake Pressure (PIP) of 237.77 psi, 4CU 2AL cable and 68% pump efficiency. With the amount of oil production increasing to 702 BOPD, the rate of oil that can be produced is 1338 BOPD. and obtained a value from the Productivity Index (PI) of 3.4 bbl/day.